EASR: Graph-based Framework for Energy Efficient Smart Routing in MANET using Availability Zones - Ramanna Havinal; Girish V Attimarad; M N Giriprasad (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Energy consumption in MobileAdhoc Network (MANET) is a topic of research from more than a decade. Althoughthere are multiple archival of literatures, that have proposed variousenergy-efficient algorithms for reducing the energy consumption to improveenergy efficiency. Establishing correct and reliable route is important designissue in MANET, but a more challenging goal is to provide energy efficientroute. But, it was observed that majority of such energy efficient routingprotocols just give symptomatic solution which addresses and mitigated theenergy issues overlooking various associated issues like quality of services.Moreover, in majority of research previous studies it is found that AODV andDSDV are highly in adoption rate among the researcher for solving energy issuesusing routing protocols. This manuscript after reviewing some of thesignificant literatures in past explored issues in existing AODV and DSDVand  proposes a novel energy efficientrouting protocols by incorporating a new actor called availability zone. Theproposed model shows better energy efficiency and QoS compared to AODV andDSDV.